Out of Canada: Images of Africa in Contemporary Canadian Culture - Stratton, Florence (Studies in Canadian Literature, 2001)
Through a consideration of representations of Africa in recent European-Canadian fiction, specifically Jennifer Mitton's Fadimatu, Audrey Thomas's Coming Down from Wa, and Barbara Gowdy's The White Bone, as well as public commentary in English, one can begin to answer the question, "what does Africa mean in contemporary Canadian culture?" Doing so allows for an examination of the relationship between the images of Africa in contemporary Canadian culture and European colonial representations of Africa. Studies by Dorothy Hammond and Alta Jablow, Christopher L. Miller, and V.Y. Mudimbe are particularly useful in providing a framework for a study of what has come to be called Africanist discourse, and its operation as an instrument of power.